Profiling engineering students' receptive vocabulary in Malaysian polytechnics / Suzana Ahmad ... [et al.] - Ahmad, Suzana; Kumar, Jeya Amantha; Mohamad, Mariam; Sanusi, Anna Mardeia (Universiti Teknologi MARA, Kedah, 2023)
Receptive vocabulary knowledge plays an important role in providing a broader ability for language learners to comprehend reading texts and contributes to the comprehension of utterances. Knowledge of the learners' vocabulary level is essential, not only as an indicator of the learners' linguistic ability but also for planning and setting goals in language learning. This study aims to investigate the English language receptive vocabulary knowledge of POLIMAS engineering students in terms of word levels. The Vocabulary Levels Test (VLT) was administered to 111 engineering students to measure their receptive vocabulary knowledge at five different word levels in VLT. The results reveal that more than half of the students possess a low level of receptive vocabulary as they failed to receive a minimum score of 26 for all word levels in the test. The findings highlight the need to raise instructors' awareness of learners' vocabulary and suggestions for effective guidance in enhancing students' vocabulary knowledge.